Hubungan antara Dukungan Keluarga, Pengetahuan dan Perilaku Ibu Hamil terhadap Tingkat Kecemasan Ibu Hamil Jelang Persalinan - Fadilla, Halida; Anggraeni, Milka; Hidayani, Hidayani (MPI Press, 2024)
Background: Every year, 373 million pregnant women in Indonesia experience anxiety. Around 28.7 percent of all pregnant women experience anxiety. This number is equivalent to 107,000,000 people worldwide. The effects of maternal anxiety on fetal development have been well documented. Several things that can influence the level of anxiety are family support and the mother's knowledge. This support and knowledge will then become a pattern of behavior for pregnant women. Objective: To determine the relationship between family support, knowledge and behavior of pregnant women on anxiety of pregnant women before giving birth in PMB A Leuwiliang District. Bogor. Method: This research is a quantitative study using a cross-sectional approach with total sampling and the number of samples taken was 50 respondents. Data collection techniques use questionnaire media. Bivariate analysis was carried out to obtain information on whether there was a correlation between the independent variable and the dependent variable using chi-square.Results: The results of this study show a relationship between family support and anxiety with a p-value <0.001. The relationship between knowledge and anxiety with p-value <0.001. The relationship between behavior and anxiety with p-value <0.001. Conclusion: There is a relationship between family support, knowledge and behavior of pregnant women on anxiety of pregnant women before giving birth at PMB A Leuwiliang, Bogor Regency. Therefore, all pregnant women should have family support and good knowledge in order to reduce the level of anxious behavior in facing childbirth.